The Impact of International Tourism on Economic Growth and Carbon Dioxide Emission in Asean Five Country - Aulia Hapsari Juwita; Suryanto Suryanto; Bhimo Rizky Samudro (Universitas Ahmad Dahlan, 2021)
The purpose of this paper is the international tourism have impact on economic growth and carbon dioxide (CO2) emissionsin ASEAN Five (Indonesia, Malaysia, Philippines, Thailand, Singapore) or not. There are increase in tourism receipts, GDP, and FDI as well as CO2 emissions approximately 9%, 5%, 4% and 26% respectively. They are always increasing, but is there any relation between international tourism, GDP and carbon dioxide (CO2). This research employs data from 1995 to 2018 to examine long-run equilibrium relationships between tourism, CO2, economic growth and foreign direct investment (FDI). Panel analysis with unit root and cointegration test approachis utilized. This paper found that there is a long-term equilibrium relationships between each variable.The tourism receipt, FDI and CO2 emissions affect economic growth positively and statistically significant. In addition, economic growth affect CO2 emissions while tourism does not affect CO2 and FDI indicates a negative relationship on CO2 emissions. Finally, the paper reveals that international tourism receipt affect economic growth but does not affect CO2.